Organocatalytic asymmetric cascade reaction of gamma-substituted deconjugated butenolides with o-formyl-beta-nitrostyrene - Deepake, Siddharth K.; Lanjewar, Atul B.; Thatikonda, Thanusha; Gonnade, Rajesh G.; Das, Utpal (ChemistrySelect, 2018)
An efficient chemo-, diastereo- and enantio-selective cascade synthesis of functionalized indanols bearing four contiguous stereogenic centres has been developed via the reaction of beta,gamma-butenolides with o-formyl-beta-nitrostyrenes in the presence of bi-functional hydrogen-bonding catalyst. Indanol derivatives containing gamma,gamma-disubstituted butenolides were obtained in good yields and with moderate to high enantioselectivities/diastereoselectivities.
Keywords: butenolides; Cascade reaction; Enantioselectivity; Indanol; organocatalysis